Práticas de cuidado de puérperas quilombolas à luz da teoria transcultural - Lucena , Tâmara Silva de (2019)
This study had as object of study the care practices of quilombola women in the postpartum period. The puerperium is characterized by being a remarkable stage in the life of the woman, permeated by local and systemic changes, from pregnancy and childbirth, where the woman's organism returns to its pre-gravid state; as well as psychosocial changes, demonstrating that this period needs comprehensive assistance. Therefore, it is in this integrality of care that the beliefs, values and cultures that each woman possesses are inserted and that they will directly influence their care practices. These influences are learned and transmitted between generations, aiming at the health and well-being of puerperal women. The aim of this study was to identify care practices in the puerperium of quilombola women in light of the Leininger Transcultural Theory. Research of a qualitative nature, based on the ethno - inference and theoretical framework of the Theory of Diversity and Universality of Care of Madeleine Leininger, held in the Quilombola Muquém Remnant Community, in the municipality of. Fourteen quilombola women who had experienced the puerperal period participated in the study. The research was approved by the Research Ethics Committee, under the no. 2,725,381 opinion. The information was collected from June to September of 2018 with the immersion of the researcher in the field, following the steps of the methodological path of the ethno-inference, using the enabling guide of Observation-Participation-Reflection, a socio-demographic data form, semi-structured interview and the field diary. The analysis of the information was carried out by means of the guide of analysis suggested by Leininger, through the ethnographie. From the analysis of the information emerged four thematic units: Knowing the participants of the research; Care practices based on local culture, Care practices from the perspective of healing, and Practices of care versus professional care. Therefore, the knowledge and practices carried out by the quilombola women were aimed at the non-sickness of these women in this period, because if they had any complications during this period, it would probably leave sequels for the rest of their lives, demonstrating that postpartum care does not only involve physiological dimension, but also sociocultural, which will be surrounded by various factors, such as religious, technological, political, economic, educational and kinship.